2018
DOI: 10.1039/c8ta06057f
|View full text |Cite
|
Sign up to set email alerts
|

Hierarchical 3D macrosheets composed of interconnected in situ cobalt catalyzed nitrogen doped carbon nanotubes as superior bifunctional oxygen electrocatalysts for rechargeable Zn–air batteries

Abstract: Novel hierarchical 3D macrosheets composed of cobalt catalyzed nitrogen doped carbon nanotubes exhibit superior bifunctional oxygen catalysis and can act as a highly durable cathode for rechargeable Zn–air batteries.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
32
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 64 publications
(32 citation statements)
references
References 56 publications
0
32
0
Order By: Relevance
“…The over potential at a current density of 10 mA/cm 2 for the Co‐NCNT catalyst is 1.63 V, which is only slightly lower than the commercial RuO 2 catalysts with 1.59 V (Figure S6E), showing the excellent OER performance for the Co‐NCNT catalyst. As shown in Figure S6F, the Co‐NCNT catalyst showed the potential gap of 0.83 V between the half‐wave potential for ORR and potential at 10 mA/cm 2 for OER, implying the Co‐NCNT catalyst is a potential bifunctional oxygen electrocatalyst 44,45 …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The over potential at a current density of 10 mA/cm 2 for the Co‐NCNT catalyst is 1.63 V, which is only slightly lower than the commercial RuO 2 catalysts with 1.59 V (Figure S6E), showing the excellent OER performance for the Co‐NCNT catalyst. As shown in Figure S6F, the Co‐NCNT catalyst showed the potential gap of 0.83 V between the half‐wave potential for ORR and potential at 10 mA/cm 2 for OER, implying the Co‐NCNT catalyst is a potential bifunctional oxygen electrocatalyst 44,45 …”
Section: Resultsmentioning
confidence: 99%
“…As shown in Figure S6F, the Co-NCNT catalyst showed the potential gap of 0.83 V between the half-wave potential for ORR and potential at 10 mA/cm 2 for OER, implying the Co-NCNT catalyst is a potential bifunctional oxygen electrocatalyst. 44,45 To test the performance of the as-prepared CC-A-N@Co-NNCTs in rechargeable ZABs, a ZAB with the material as self-standing air electrode, zinc foil as the anode, and a 6M KOH and 0.2M ZnCl 2 mixed aqueous solution as the electrolyte was constructed ( Figure 3A). The discharge performance of the ZABs was first explored, and comparison was made with similar cells of different air electrodes.…”
Section: Resultsmentioning
confidence: 99%
“…It can be seen that the Co@C hybrid was formed in the core after ZIF-67 was pyrolyzed under 873 K in an Ar atmosphere. In addition, some carbon nanotubes can be observed on the surface of the Co@C@SiO 2 -0 catalyst because the generated cobalt can catalyze the production of carbon nanotubes during the pyrolysis process [18] . However, the amount of carbon nanotubes decreased as the shell thickness increased, and the surfaces became smooth.…”
Section: Samplementioning
confidence: 99%
“…It is believed that the PC itself was the carbon source, and the introduced trace elements were the possible active domains for catalyzing or promoting the growth of CNTs from volatile organic compounds arising from decomposition of the coal. It is known that transition metals such as Fe, Co, Ni promote CNT growth [32][33][34] . Interestingly, here we found that Al, Ca, and K can also facilitate the growth of CNTs.…”
Section: Resultsmentioning
confidence: 99%